Study of the working conditions in libraries of Quito city and the exposure of its workers to fungi - Morales Carrera, Rosa; Chalán Paladínez, Remigio (Enfoque UTE, 2017)
<td style="border-style: solid; background-color: rgb(100.000000%, 100.000000%, 100.000000%); border-right-color: rgb(0.000000%, 0.000000%, 0.000000%); border-bottom-color: rgb(0.000000%, 0.000000%, 0.000000%); border-left-color: rgb(0.000000%, 0.000000%, 0.000000%); border-width: 0.000000pt 0.000000pt 0.006000pt 0.000000pt;"> The aim was to establish the risk determinants of the library workers in Quito city, due to fungi exposure. Data were collected on infrastructure conditions and work organization, measurements of temperature, relative humidity, lighting and ventilation. The microbial load of fungi in air, surfaces of documentary goods and gloves of manipulators was determined; In 5 libraries of the Equinoctial Technological University, Quito. The research showed the temperature and relative humidity of the library environments is suitable. The ventilation system <td style="border-style: solid; background-color: rgb(100.000000%, 100.000000%, 100.000000%); border-top-color: rgb(0.000000%, 0.000000%, 0.000000%); border-right-color: rgb(0.000000%, 0.000000%, 0.000000%); border-left-color: rgb(0.000000%, 0.000000%, 0.000000%); border-width: 0.006000pt 0.000000pt 0.000000pt 0.000000pt;"> is not appropriate, so it promotes dust accumulation on physical archives, It was also evidenced that workers do not know about any risk prevention procedures. The microbial contamination in the air is low and it is high in the handlers’ gloves; in the books surface microbial load has a direct relationship with the amount of accumulated dust. Some types of pathogenic opportunistic allergenic fungi, like: Cladosporium, Aspergillus and Penicillium, among others were identified. In conclusion, the biological risk due to fungi exposure is moderate because the exposure mechanism is through contact with the physical archives and the fungi presence is determined by the lack of an adequate ventilation system, physical archives preventive conservation programs, facility maintenance plans and safety and work risk training.